Challenges Caused by the COVID-19 Quarantine for Families Raising Children with Disabilities: Compatibility Between Working from Home and Childcare - Gardziuleviciene, Laura; Raisiene, Agota Giedre (European Scientific Journal, ESJ, 2021)
Parents with children having special needs go through extremely difficult emotional, psychological experiences and physical fatigue due to unavailability of help and lack of access to social services. The COVID-19 pandemic has worsened the situation since the need for cohesion and the importance of social responsibility were not addressed well by the public authorities. The unavailability of help is believed to have plunged parents even further into exclusion. If before the pandemic, parents felt stigmatized, the situation after the COVID-19 pandemic became significantly worse. Thus, with the help of the phenomenological research, we aimed to reveal the challenges faced by families raising children with disabilities in combining aspects of work and childcare, by analyzing the attitudes and experiences of the respondents. The study is relevant for both public authorities and parents raising children with special needs in the context of developing social inclusion and family support network respectively.